2019
DOI: 10.1002/mpr.1762
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special issue: The WHO World Mental Health International College Student (WMH‐ICS) initiative

Abstract: Most mental disorders have their first onset in early adulthood. Epidemiological research, as well as research on preventive and early interventions, is therefore very important. This thematic issue focuses on one of the first systematic attempts to develop such services for college students. The WHO World Mental Health International College Student (WMH‐ICS) initiative is based on the largest and continuously growing epidemiological dataset ever collected in college students. Based on these results, the initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 12 publications
1
43
0
4
Order By: Relevance
“…This study was carried out as part of the WHO World Mental Health International College Student (WMH‐ICS) initiative (WMH‐ICS, ). The WMH‐ICS aims to obtain accurate cross‐national information on the prevalence, incidence, and correlates of mental, substance, and behavioural problems among college students worldwide; to describe patterns of service use, barriers to treatment, and unmet need for treatment; to investigate the associations of these disorders with role function in academic and other life domains; to evaluate the effects of a wide range of preventive and clinical interventions on student mental health, functioning, and academic performance; and to develop precision medicine clinical decision support tools to help select the right interventions for the right students (see Cuijpers et al, ). The WHM‐ICS's meta‐analysis initiative and this specific study have both been registered with PROSPERO (CRD42017068758; CRD42018090259).…”
Section: Methodsmentioning
confidence: 99%
“…This study was carried out as part of the WHO World Mental Health International College Student (WMH‐ICS) initiative (WMH‐ICS, ). The WMH‐ICS aims to obtain accurate cross‐national information on the prevalence, incidence, and correlates of mental, substance, and behavioural problems among college students worldwide; to describe patterns of service use, barriers to treatment, and unmet need for treatment; to investigate the associations of these disorders with role function in academic and other life domains; to evaluate the effects of a wide range of preventive and clinical interventions on student mental health, functioning, and academic performance; and to develop precision medicine clinical decision support tools to help select the right interventions for the right students (see Cuijpers et al, ). The WHM‐ICS's meta‐analysis initiative and this specific study have both been registered with PROSPERO (CRD42017068758; CRD42018090259).…”
Section: Methodsmentioning
confidence: 99%
“…In preparation for developing a series of interventions to address these problems, we carried out a survey to estimate prevalence of common mental disorders and correlates of mental healthcare utilisation among first-year students at two historically "White" universities in SA. This work was carried out as part of the WHO World Mental Health International College Student Initiative (WMH-ICS) [10]. We were particularly interested in potential inequalities in service utilisation among groups of students that have been historically marginalized from higher education in SA, including those who identify as Black, female, disabled, and firstgeneration students.…”
Section: Inequality and Mental Healthcare Utilisation Among First-yeamentioning
confidence: 99%
“…A different approach has been taken in the WHO World Mental Health International College Student (WMH‐ICS) initiative which takes its starting point in the collection, analysis and dissemination of epidemiological information using bona fide instruments on student mental health and targeting a defined sampling frame of students (see Cuijpers et al, ). Based on a sample of 13,984 students with a weighted mean response rate of 45.5%, Bruffaerts et al () reported the lifetime prevalence of depression and anxiety to be 21.2% and 18.6%, respectively.…”
Section: Definitions: Psychological Wellbeing and Mental Healthmentioning
confidence: 99%
“…The mental health of students in national and international higher education (HE) settings is recognised as an important public health issue (e.g., Brown, ; Holm‐Hadulla & Koutsoukou‐Argyraki, ; also see comprehensive review by Sharp & Theiler, ). A range of organisations in Australia (Orygen & The National Centre of Excellence in Youth Mental Health, ), Canada (Beckett, Bertolo, MacCabe, & Tulk, ) and the US (American College Health Association, ) have produced reports raising concerns about students’ wellbeing and mental health, in addition to reports and surveys published in the UK—for example The Insight Network and Dig‐in ()—and also recent special issues of journals devoted to student mental health (see Brown, ; Cuijpers et al, ). In the UK, key initiatives have included funding from UK Research and Innovation to support a research network focusing specifically on student mental health (see Student Mental Health Research Network; SMarTeN, https://www.smarten.org.uk/), as well as a 2018 government‐initiated directive to establish a University Mental Health Charter (Student Minds, ; https://www.studentminds.org.uk/charter.html).…”
Section: Introductionmentioning
confidence: 99%